1978
DOI: 10.1084/jem.147.3.952
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E production by human blood monocytes and mouse peritoneal macrophages.

Abstract: Purified populations of both human peripheral blood monocytes and murine peritoneal macrophages synthesize and release Prostaglandin E in vitro. In contrast, prostaglandin E was detected in neither the supernate fluids from cultures of highly enriched human lymphocytes and granulocytes, nor in nonadherent murine peritoneal cells. Macrophage prostaglandin E production was markedly enhanced by endotoxin, and completely suppressed by indomethacin. All neoplastic monocyte-macrophage cell lines examined elaborated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(102 citation statements)
references
References 20 publications
3
99
0
Order By: Relevance
“…Other work from our laboratory has demonstrated that monocytes directly resorb both devitalized bones by a mechanism which is not mediated by the action of osteoclasts (25) and live bones through an osteoclast-mediated mechanism which is prostaglandin-dependent (26). There is also other evidence which suggests that monocytes and macrophages synthesize and release PGs (27)(28)(29), collagenase (30), and hydrolytic enzymes (31), which are all capable of resorbing bone or degrading bone matrix. It is also possible that circulating mononuclear cells may transform or differentiate into osteoclasts (32).…”
Section: Discussionmentioning
confidence: 99%
“…Other work from our laboratory has demonstrated that monocytes directly resorb both devitalized bones by a mechanism which is not mediated by the action of osteoclasts (25) and live bones through an osteoclast-mediated mechanism which is prostaglandin-dependent (26). There is also other evidence which suggests that monocytes and macrophages synthesize and release PGs (27)(28)(29), collagenase (30), and hydrolytic enzymes (31), which are all capable of resorbing bone or degrading bone matrix. It is also possible that circulating mononuclear cells may transform or differentiate into osteoclasts (32).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a tested alone was ineffective. IFN-q and PGE2 are known to be produced by monocytes (21,22), which therefore may account for the suppression of IgE production observed in the presence of relatively high monocyte concentrations (data not shown). These data indicate that factors that inhibit CD23 induction by IL-4 on B cells also blocked IL-4-induced IgE production, which suggests an assoqiation between CD23 expressed on B cells and IgE production.…”
Section: Methodsmentioning
confidence: 99%
“…Of particular importance is the ability of macrophages to act as a source of prostaglandins, which are potent inhibitors of several lymphocyte functions, such as mitogenesis (Goodwin, Bankhurst & Messner, 1977), cytolysis (Lichtensteine; a/., 1972; Koga et al, 1982), lymphokine production (Gordon, Bray & Morlcy, 1976), and proliferation (Stout & Fisher, 1982). The principal inhibitory prostaglandins released by suppressor macrophages appears to be those ofthe E series (PGEi, PGE2) (Humes et al, 1977;Kurland & Bockman, 1978;Stenson & Parker, 1980), the production of which is blocked by indomethacin. Our results thus provide a further example of the correlation between a suppressive effect of macrophages and their ability to release prostaglandins; they suggest a role for both in modulating liver graft rejection in the critical period after grafting when tolerance is becoming established.…”
Section: Discussionmentioning
confidence: 99%